Spanish Validation of the PICCOLO (Parenting Interactions With Children: Checklist of Observations Linked to Outcomes) - Vilaseca, Rosa; Rivero, Magda; Bersabé, Rosa M.; Navarro-Pardo, Esperanza; Cantero, Maria Jose; Ferrer, Fina; Valls Vidal, Clara; Innocenti, Mark S.; Roggman, Lori (Frontiers in Psychology, 2019)
Background/Objective: The aim of this study was to explore the psychometric properties of the Spanish version of the Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO; Roggman et al., 2013b). This observational measure is composed of 29 items that assess the quality of four domains of parenting interactions that promote child development: affection, responsiveness, encouragement, and teaching. Method: The sample included 203 mother-child dyads who had been video-recorded playing together. Fifty-six percent of the children were male, and 44% were female, aged from 10 to 47 months. Video-recorded observations were rated using PICCOLO items. Results: Confirmatory factor analysis supported that the instrument has four first-order factors corresponding to the hypothesized domains of parenting behaviors, and a second-order factor corresponding to a general factor of positive parenting. Construct validation evidence was compiled by examining the relationship between PICCOLO scores and child age. As expected, teaching domain and total PICCOLO scores were positively correlated with child age. The Spanish PICCOLO also demonstrated good interrater reliability (ranging from .69 to .84) and internal consistency reliability (ranging from .59 to .88) for the four domain scores and the total parenting score. Concurrent criterion-related validity was examined via correlations between parenting scores and child cognitive, language and motor skills outcomes, measured using the Bayley Scales of Infant Development. Conclusions: The Spanish version of the PICCOLO meets the criteria for a reliable and valid observational measurement of parenting interactions with children. The psychometric properties of the instrument make it appropriate for general research purposes, but also for program evaluation of Early Intervention and other parenting-support interventions. This measure, focused on parent strengths, could be used to facilitate family-centered practices in early intervention and other programs that have parenting as an outcome.